2018
DOI: 10.1016/j.ijdevneu.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Swimming exercise before and during pregnancy: Promising preventive approach to impact offspring's health

Abstract: Several environmental factors affect child development, such as the intrauterine environment during the embryonic and fetal development and early postnatal environment provided by maternal behavior. Although mechanistic effects of maternal exercise on offspring health improvement are not yet completely understood, the number of reports published demonstrating the positive influence of maternal exercise have increase. Herein, we addressed issues related to early postnatal environment provided by maternal behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…Maternal exercise during pregnancy as a positive maternal behavior has been extensively investigated [20][21][22][23]. The present study aimed to investigate the effect of physical activity of mothers as a healthy lifestyle on the health of offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal exercise during pregnancy as a positive maternal behavior has been extensively investigated [20][21][22][23]. The present study aimed to investigate the effect of physical activity of mothers as a healthy lifestyle on the health of offspring.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of Developmental Origins of Health and Disease research (DOHaD) defines that health and disease risk development in the next generations is affected by parental environmental milieu. In this context, we and other groups have shown that events occurring during the development period may positively or negatively influence health throughout life (Agosti, Tandoi, Morlacchi, & Bossi, 2017; August et al., 2018; Klein et al., 2018; Langley‐Evans, 2015).…”
Section: Introductionmentioning
confidence: 85%
“…Similarly, Klein et al demonstrated that swimming before gestation does not affect the body weight of pregnant female rats. 34 Although swimming has been used as a stressor in repeated variable stress paradigms, 35,36 studies have also shown its use as a form of exercise, demonstrating positive neural adaptations, in addition to decreasing corticosterone levels. 37,38 There is also evidence that mothers who perform physical activities from the beginning of the gestation period and then decrease the exercise levels closer to birth generate significantly heavier children, probably due to the increase in the body fat percentage.…”
Section: Discussionmentioning
confidence: 99%